Rural Households' Demand for Frankincense Forest Conservation in Tigray, Ethiopia: A Contingent Valuation Analysis. (26th March 2013) - Tilahun, M.; Vranken, L.; Muys, B.; Deckers, J.; Gebregziabher, K.; Gebrehiwot, K.; Bauer, H.; Mathijs, E.
Abstract: Frankincense from Boswellia papyrifera forest (BPF) is a traded commodity used in the pharmaceutical, food, cosmetic and chemical industries. Ethiopia is an important producer of frankincense, but the resource is under continuous degradation and requires conservation. We applied a contingent valuation to assess rural households' willingness to pay and willingness to contribute labor for BPF conservation. Next to the bid, willingness to pay is influenced most by income, education, and willingness to contribute labor by family labor and gender of the household head. A household is willing to pay at least 4·86 or contribute 7·17 labor days per year, which amounts to 6·64 at per capita daily income. This suggests that using per capita daily income rather than market wage rates could result in convergence in response asymmetry of labor and cash payment vehicles. The potential local demand for conservation of BPF could be mobilized effectively with complementary policy interventions aimed at sustainable use and poverty reduction. Copyright © 2013 John Wiley & Sons, Ltd.